Improper protein trafficking contributes to artemisinin sensitivity in cells lacking the KDAC Rpd3p. Issue 21 (27th September 2014) - Jensen, Amornrat Naranuntarat; Chindaudomsate, Worathad; Thitiananpakorn, Kanate; Mongkolsuk, Skorn; Jensen, Laran T.
Abstract : Lysine deacetylases (KDACs) inhibitors may have therapeutic value in anti‐malarial combination therapies with artemisinin. To evaluate connections between KDACs and artemisinin, Saccharomyces cerevisiae deletion mutants in KDAC genes were assayed. Deletion of RPD3, but not other KDAC genes, resulted in strong sensitivity to artemisinin, which was also observed in sit4 Δ mutants with impaired endoplasmic reticulum (ER) to Golgi protein trafficking. Decreased accumulation of the transporters Pdr5p, Fur4p, and Tat2p was observed in rpd3 Δ and sit4 Δ cells. The unfolded protein response is induced in rpd3 Δ cells consistent with retention of proteins in the ER. Disruption of protein trafficking appears to sensitize cells to artemisinin and targeting these pathways may be useful as part of artemisinin based anti‐malarial therapy. Abstract : Deletion of RPD3 results in sensitivity to the anti‐malarial drug artemisinin in glycerol medium. Strains deleted for SIT4, with impaired ER to Golgi transport, exhibit artemisinin sensitivity. Pdr5p, Fur4p and Tat2p protein levels are substantially reduced in rpd3 Δ and sit4 Δ cells. The unfolded protein response is induced in rpd3 Δ, consistent with retention of proteins in the ER. ER stress may enhance the sensitivity of cells to artemisinin toxicity.